(untitled) (Research Nepal Journal of Development Studies, 2024)
This study critically examines the persistent influence of caste and ethnicity on development in rural Nepal. Employing a qualitative, historical-narrative design based on secondary sources, the research reveals a stark divergence between constitutional ideals of an inclusive society and the enduring realities of deep-rooted inequality. The analysis identifies a historical continuum of state-sponsored hierarchy, originating with the 1854 Muluki Ain which legally codified a rigid caste structure to centralize power within a Parbatiya (Brahmin-Chhetri) elite. This legacy institutionalized a political economy where resource control, particularly land, was concentrated among high castes, systematically marginalizing ethnic groups (Janajatis) and Dalits as a dependent labor force. Consequently, contemporary development initiatives, even when well-intentioned, often perpetuate these historical inequities. Implemented through local elites, such projects are frequently co-opted by those with pre-existing social and economic capital, reinforcing a cycle of exclusion. Furthermore, the research demonstrates the remarkable resilience of social hierarchies despite progressive legal reforms, including the 2015 constitution. While legal frameworks now prohibit discrimination, deeply ingrained ideologies of ritual purity and pollution persist, manifesting in ongoing social practices that impede marginalized groups’ access to resources and opportunities. Awareness campaigns and NGO interventions have proven insufficient to dismantle these foundational power dynamics. The study concludes that without directly confronting these entrenched social and historical structures, policy mandates alone will remain inadequate for achieving genuinely inclusive and equitable development in Nepal.